2023
DOI: 10.1038/s41467-023-38318-7
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 inhibition overcomes cisplatin resistance by blocking autophagy-mediated hyperactivation of EGFR signaling pathway

Abstract: Cisplatin resistance along with chemotherapy-induced neuropathic pain is an important cause of treatment failure for many cancer types and represents an unmet clinical need. Therefore, future studies should provide evidence regarding the mechanisms of potential targets that can overcome the resistance as well as alleviate pain. Here, we show that the emergence of cisplatin resistance is highly associated with EGFR hyperactivation, and that EGFR hyperactivation is arisen by a transcriptional increase in the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…However, cisplatin resistance is a common issue in bladder cancer treatment, often leading to poor treatment efficacy [ 22 ]. Several studies have revealed that autophagy plays a crucial role in mediating cisplatin resistance [ 23 , 24 , 25 ], and inhibiting autophagy can enhance the sensitivity of bladder cancer cells to cisplatin [ 13 ]. In this study, we successfully developed cisplatin-resistant T24/DDP cell lines derived from bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, cisplatin resistance is a common issue in bladder cancer treatment, often leading to poor treatment efficacy [ 22 ]. Several studies have revealed that autophagy plays a crucial role in mediating cisplatin resistance [ 23 , 24 , 25 ], and inhibiting autophagy can enhance the sensitivity of bladder cancer cells to cisplatin [ 13 ]. In this study, we successfully developed cisplatin-resistant T24/DDP cell lines derived from bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, studies have focused on combination treatments. One study has shown that cisplatin susceptibility in tumors can be achieved by the inhibition of transient receptor potential vanilloid 1 (TRPV1), which is a nonselective cationic channel regulating Ca 2+ influx [148]. Interestingly, various tissues like the brain, kidney, bronchial epithelial cells and others show the wide expression of TRPV1, and these organs are damaged by the severe cytokine storm of COVID-19.…”
Section: Future Perspectives: Potential Aims and Experimental Methodsmentioning
confidence: 99%